International cooperation in fight with hunger in timeless of Medieval Rus - Прохазка, Г. А. (Theory and practice of jurisprudence, 2016)
The article discusses the features of the international cooperation in the fight with hunger during the medieval Kyiver Rus. The forms of the interaction of medieval societies and the ways of international helping of the nations are investigated in the case of the malnutrition and the hunger